METODE TEOLOGI GUSTAVE THILS - F. Purwanto (Jurnal Orientasi Baru, 2011)
Historical-critical method had a particular place in the renewal of theologyat the dawn of the Second Vatican Council. This method brings theology intoa direct contact with the sources investigated. Such a step enables theology torediscover the richness of the life of the Church, altogether with its developmentand limitations. Gustave Thils, a Belgian theologian, who participated in thediscussions during the Council on the topic of ecumenism, the Episcopal serviceand Roman Pontiff, as well as the discussion of the Scheme XIII, made use thismethod in his theological adventure. This approach provides a firm basis fora theological hermeneutic. Historical-critical method enables theology to beliberated from fundamentalism and liberalism tendencies. A development ofunderstanding which is slow but sure is well supported by this method.